2015
DOI: 10.1021/acs.est.5b01040
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biological Release of Poly- and Perfluoroalkyl Substances (PFASs) from Municipal Solid Waste in Anaerobic Model Landfill Reactors

Abstract: A wide variety of consumer products that are treated with poly- and perfluoroalkyl substances (PFASs) and related formulations are disposed of in landfills. Landfill leachate has significant concentrations of PFASs and acts as secondary point sources to surface water. This study models how PFASs enter leachate using four laboratory-scale anaerobic bioreactors filled with municipal solid waste (MSW) and operated over 273 days. Duplicate reactors were monitored under live and abiotic conditions to evaluate influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 40 publications
(102 reference statements)
2
81
0
Order By: Relevance
“…Correct identification and monitoring of the actual PFAS constituents present in anaerobic environments such as sediments, groundwater, and leachates are of critical importance for properly assessing remediation efforts and for evaluating ecotoxicological impacts. The identification of MeFBSAA as an end product in anaerobic sludge cultures helps provide some clarity to the presence of MeFBSAA in leachate from anaerobic landfill simulation tests [34,35] and the recent detection of MeFBSAA and PFBSI in river sediments [23]. Similarly, the identification of EtFOSAA and PFOSI from EtFOSE can explain the determination of EtFOSAA as a major PFAS in sediment, soil, and sludge samples [32,33].…”
Section: Environmental Implicationsmentioning
confidence: 96%
See 4 more Smart Citations
“…Correct identification and monitoring of the actual PFAS constituents present in anaerobic environments such as sediments, groundwater, and leachates are of critical importance for properly assessing remediation efforts and for evaluating ecotoxicological impacts. The identification of MeFBSAA as an end product in anaerobic sludge cultures helps provide some clarity to the presence of MeFBSAA in leachate from anaerobic landfill simulation tests [34,35] and the recent detection of MeFBSAA and PFBSI in river sediments [23]. Similarly, the identification of EtFOSAA and PFOSI from EtFOSE can explain the determination of EtFOSAA as a major PFAS in sediment, soil, and sludge samples [32,33].…”
Section: Environmental Implicationsmentioning
confidence: 96%
“…However, some researchers have found that under certain physiological conditions EtFOSE biotransformation is incomplete and exclusively yields N-ethyl perfluorooctanesulfonamido acetate (EtFOSAA) and perfluorooctane sulfinate (PFOSI) and not PFOS [31]. The analogous anticipated MeFBSE biotransformation product N-methyl perfluorobutanesulfonamido acetate (MeFBSAA) was recently identified in leachate from anaerobic landfill simulation tests with municipal solid wastes, and levels appeared to increase over time [34], suggesting that biotransformation of MeFBSE in anaerobic waste may occur. The analogous anticipated MeFBSE biotransformation product N-methyl perfluorobutanesulfonamido acetate (MeFBSAA) was recently identified in leachate from anaerobic landfill simulation tests with municipal solid wastes, and levels appeared to increase over time [34], suggesting that biotransformation of MeFBSE in anaerobic waste may occur.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations